Acquired Thrombotic Thrombocytopenic Purpura After ChAdOx1 nCoV-19 Vaccine: A Case Report - Domenica Caramazza; Marco Salvini; Vincenzo Saturni; Francesco Ripamonti; Michele Merli; Benedetta Bianchi; Stefania Agnoli; Davide Sirocchi; Barbara Mora; Elena Galfrascoli; Francesco Passamonti (Annals of Internal Medicine: Clinical Cases)
COVID-19, the illness caused by SARS-CoV-2, continues to cause significant morbidity and mortality across the world. An important step in overcoming SARS-CoV-2 is the global vaccination plan. Cases of acquired thrombotic thrombocytopenic purpura (aTTP) have been recently described after SARS-CoV-2 vaccination. We describe a patient case of aTTP occurring 25 days after ChAdOx1 nCov-19 (Vaxzervria/AstraZeneca) vaccination that was promptly treated with plasma exchange, corticosteroids, rituximab, and caplacizumab. Remission of aTTP was achieved in 2 weeks and the patient is currently in complete remission.